PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BAHTERA ENERGI SAMUDRA TUAH JAKARTA SELATAN - Setiyono, Agus; Japanis Permatasari, Retno (Journal of Research and Publication Innovation, 2024)
This study aims to determine the simultaneous influence of training and work discipline on employee performance at PT Bahtera Energi Samudra Tuah South Jakarta. The method used is quantitative associative. The research population is 70 00 and all of them are sampled in this study. The data analysis techniques used are instrument test, classical assumption test, descriptive analysis, regression test, correlation coefficient test, determination coefficient test and hypothesis test. The results of the study showed that training had a significant effect on employee performance by 30.7% while the remaining 69.3% was influenced by other variables that were not studied. Work discipline generally affects employee performance by 17.1% while the remaining 82.9% is influenced by other variables that are not studied. Training and work discipline simultaneously affected employee performance by 37.8% while the remaining 62.2% were influenced by other variables that were not studied. The results of the study showed that the multiple liner regression equation Y = 14.617+0.423 X1+0.223 X2 means that employee performance even without the influence of training and work discipline already has an influence of 14.617. Simultaneously, training and work discipline have a positive and significant effect on employee performance, this is evidenced by the value of F calculation > F table, which is (20.364 > 3.13) with a significance of 0.000 < 0.05, then H0 is rejected and H3 is accepted, meaning that there is a positive and significant influence between training and work discipline on employee performance simultaneously at PT Bahtera Energi Samudra Tuah South Jakarta.